2017
DOI: 10.1249/mss.0000000000001067
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Stiffness Changes after Concussion in Collegiate Football Players

Abstract: Purpose Recent research indicates that a concussion increases risk of musculoskeletal injury. Neuromuscular changes following concussion might contribute to the increased risk of injury. Many studies have examined gait post-concussion, but few studies have examined more demanding tasks. This study compared changes in stiffness across the lower extremity, a measure of neuromuscular function, during a jump-landing task in athletes with a concussion (CONC) to uninjured athletes (UNINJ). Methods Division I footb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…28 Cognitive control refers to the subset of brain processes underlying perception, memory, and action, 8 and neuromechanical coupling refers to modulations in muscle tone that can optimize joint stiffness. 4 A subtle cognitive-control deficit could adversely affect the ability to rapidly generate muscle stiffness, which may be due to either a previous concussion 11,24 or musculoskeletal injury. 20,29 Even football players exposed to repetitive head blows that did not result in a concussion diagnosis exhibited significant reductions in ImPACT verbal memory or visual memory scores.…”
Section: Resultsmentioning
confidence: 99%
“…28 Cognitive control refers to the subset of brain processes underlying perception, memory, and action, 8 and neuromechanical coupling refers to modulations in muscle tone that can optimize joint stiffness. 4 A subtle cognitive-control deficit could adversely affect the ability to rapidly generate muscle stiffness, which may be due to either a previous concussion 11,24 or musculoskeletal injury. 20,29 Even football players exposed to repetitive head blows that did not result in a concussion diagnosis exhibited significant reductions in ImPACT verbal memory or visual memory scores.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing athletes during more challenging neuromuscular tasks that better reflect athletic demands may help identify those athletes who may continue to have deficits after concussion symptom resolution. One recent study by Dubose et al [88] investigated the effect of concussion on neuromuscular performance during a jump-landing task. Compared with baseline pre-concussion jump-landing performance, concussed subjects demonstrated increased hip stiffness and reduced knee and leg stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism for this increased risk of musculoskeletal injury after concussion is unclear. Recent evidence 11 suggested that neuromuscular function, specifically altered lower extremity muscle stiffness, may play a role in the musculoskeletal injury risk after concussion. Previous authors 5 also hypothesized that relatively smallmagnitude dynamic balance deficits may be exacerbated in the highly dynamic sport environment with significant motor and cognitive demands.…”
mentioning
confidence: 99%